Force Characterization Of A Rotary Motion Electrostatic Actuator Based On Finite Element Method (FEM) Analysis - Md Ghazaly, Mariam; Tan, Aik Choon; Che Amran, Aliza; Sato, Kaiji (Scientific.Net, 2015)
Two types of rotary motion electrostatic actuators were designed and analyzed using Finite Element Method (FEM) analysis. This paper discussed the comparisons and detailed thrust force analysis of the two actuators. Both designs have similar specifications; i.e the number of rotor’s teeth to stator’s teeth ratio, radius and thickness of rotor, and gap between stator and rotor. Two structures were designed & evaluated; (a) Side-Driven Electrostatic Actuator and (b) Bottom-Driven Electrostatic Actuator. The paper focuses on comparing & analyzing the generated electrostatic thrust force for both designs when the electrostatic actuator’s parameters are varied. Ansys Maxwell 3D software is used to design and analyze the generated thrust force of the two rotary motion electrostatic actuators. The FEM analyses have been carried out by (i) varying the actuator size; (ii), varying the actuator thickness and (iii) varying the actuator teeth ratio. The FEM analysis shows that the Bottom-Drive Electrostatic Actuator exhibit greater thrust force, 4931.80N compared to the Side-Drive Electrostatic Actuator, 240.96N; when the actuator’s radius is 700m, thickness is 50m, gap between the stator and rotor is 2m and the teeth ratio is 16:12.